Biomechanical Comparison of Anterior Lumbar Screw-plate Fixation versus Posterior Lumbar Pedicle Screw Fixation - 刘列华 郭从涛 周强 蒲小兵 宋磊 王浩明 赵晨 成仕明 兰阳军 刘岭 (Journal of Huazhong University of Science and Technology. Medical sciences, 2014)
Anterior lumbar interbody fusion （ALiF） followed by posterior pedicle screw fixation （PSF） in a second procedure is mostly used to implement lumbar spine fusion. ALIF followed by an- terior lumbar screw-plate has a lot of advantages, but its biomechanical stability requires confirma- tion. This study evaluated the biomechanical stability of a novel anterior lumbar locked screw-plate （ALLSP） by comparison with posterior lumbar PSF. Twelve fresh human cadaveric lumbar speci- mens （L4-L5） were assigned to four groups： ALIF~PSF group, ALIF＋ALLSP （both fixed） group, ALIF group and an untreated control （both non-fixed） group. The first three groups received implan- tation of a rectangular titanium cage. Tests under axial compression, flexion, extension, lateral bend- ing, or rotation showed that the fixed groups had significantly stronger stability than the non-fixed groups （P=-0.000 for all）. The ALIF＋ALLSP group had significantly greater axial stiffness under ap- plied axial compression and significantly less angular displacement under rotational forces than the ALIF＋PSF group. The angular displacement of the ALIF＋ALLSP group was less under flexion than that of the ALIF＋PSF, and the angular displacement under lateral bending and extension was greater, but these differences were not statistically significant. In summary, the ALLSP conforms to the ante- rior lumbar spine and has good biomechanical stability. It is a reliable choice for enhancing the sta- bility of ALIF.